2021
DOI: 10.1002/jnr.24849
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain changes associated with cognitive trajectories determine specific tDCS‐induced effects among older adults

Abstract: The combination of transcranial direct current stimulation (tDCS) with functional magnetic resonance imaging (fMRI) can provide original data to investigate age‐related brain changes. We examined neural activity modulations induced by two multifocal tDCS procedures based on two distinct montages fitting two N‐back task‐based fMRI patterns (“compensatory” and “maintenance”) related to high working memory (WM) in a previous publication (Fernández‐Cabello et al. Neurobiol Aging (2016);48:23–33). We included 24 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…The brain fMRI evaluations showed significant changes after both interventions in a subgroup of patients: increased activity in the right frontal medial cortex and the bilateral paracingulate gyrus. These two areas do not correspond with any of the cortical areas stimulated, however distal changes induced by tDCS and capture by fMRI activity patterns have been reported in previous investigations [40]. Increased activity in the active tDCS group was observed in the anterior cingulate/paracingulate cortex, a brain region that holds a potential role in language processing, in particular for tasks that require cognitive control.…”
Section: Discussionmentioning
confidence: 47%
“…The brain fMRI evaluations showed significant changes after both interventions in a subgroup of patients: increased activity in the right frontal medial cortex and the bilateral paracingulate gyrus. These two areas do not correspond with any of the cortical areas stimulated, however distal changes induced by tDCS and capture by fMRI activity patterns have been reported in previous investigations [40]. Increased activity in the active tDCS group was observed in the anterior cingulate/paracingulate cortex, a brain region that holds a potential role in language processing, in particular for tasks that require cognitive control.…”
Section: Discussionmentioning
confidence: 47%
“…However, some longitudinal studies ( Nyberg et al, 2010 ; Rieckmann et al, 2017 ) reported an age-related reduction in frontal activity. More specifically, older adults defined as decliners (i.e., individuals with WM performance decline across time, as opposed to so-called maintainers) showed decreased recruitment of the prefrontal cortex ( Rieckmann et al, 2017 ; Vaqué-Alcázar et al, 2020 , 2021 ). To reduce the confound of cohort effects, it might be worth contemplating the administration of routine assessment of cognitive functions throughout an individual’s life span.…”
Section: How Can Cognitive Resources In Aging Be More Reliably Measured Through Neural Indexes?mentioning
confidence: 99%